Poetry of Russian relocation-22: the main motives - Desnitsky, Andrei (Literatūra, 2023)
The article for the first time, as far as we know, introduces to the scholars’ community the poetry of “relocated” Russians (those in the process of unvoluntary change of address after the 24th of February 2022) and describes it from the motive analysis point of view. This is a new and a rather special phenomenon between literature and blogosphere which partly repeats the experience of the so called “bards’ songs” of the late Soviet period but under different circumstances and in different ways. Under total censorship and selective repressions in the Russian Federation the poetry published in social media that became one of the main means to communicate and to come through a personal crisis. One may expect that in future it may play an important role compared to that of the bard’s songs.
Keywords: relocation; anti-war poetry; bards’ songs; motif; intertextuality